PENINGKATAN KREATIVITAS DAN KEMAMPUAN MENULIS KARANGAN NARASI MELALUI PENERAPAN MODEL EXAMPLES NON EXAMPLES DENGAN MEDIA GAMBAR SERI - Nurhayati, Tri (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2019)
The research was aimed to improve students’ creativity and skill in writing narrative text in the Indonesia subject through Examples Non Examples with picture series aids. This classroom research consisted of two cycles. The object of the research was the fourth grader’s students in SDN 3 Linggasari consisted of 35 students, 19 males, and 16 females. Each cycle consisted of 4 stages, planning, implementing, observation, and reflection. The instruments used to collect the data were test and observation sheet. To see the students’ work on the narrative text, they used a test paper of narrative at the end of the meeting. It showed that Examples Non-Examples with picture series aids could improve student’s creativity and narrative writing. It could be proven from the writing outcome it first and second cycle. In the first cycle, the level of achievement was 40% an in the second cycle was 89%. The students’ creativity was also improving from the first to the second cycle. In the first cycles, it showed 57% and 86% in the second cycle. It could be drawn that Examples Non-Examples method could improve students’ creativity and narrative skill for the fourth semester SD N 3 Linggasari.